Kehujjahan Sunnah dalam Wacana Ingkar Sunnah Kamal Azmi - Reza Pahlevi Dalimunthe; Sahlan Muhammad Faqih; Wahyudi Wahyudi (Jurnal Iman dan Spiritualitas, 2021)
In the early days of Islam, the seeds of the followers of Ingkar Sunnah had appeared, namely Shi'ah and Khawarij, followed by Muktazilah. Their blasphemy in denying the Sunnah is the lust and fanaticism of their group. Ingkar Sunnah thought was not in demand for several centuries, then appeared again in the early 14th century Hijriyah. The development of the modern Ingkar Sunnah is more progressive than its predecessor. Among the driving factors is the orientalist study of the Sunnah which has influenced the views of Muslim scholars on the Sunnah. In addition, the colonialism (isti'mârî) which occurred in several countries with large Muslim majority such as India, increased the sincerity of the Orientalists to attack the Sunnah to its roots. Their efforts were successful, with the emergence of Ingkar Sunnah groups in various regions, including: Madrasah al-'Ashrâniyyah in India, Madrasah al-Qur'âniyyin in India, and Madrasah al-'Aqlâniyyah in Egypt. This study uses a qualitative method, data collection using literature study, while the approach is historical-thematic. This study found that the modern Ingkar Sunnah group was more organized than the earlier generations. Their evidence comes from the influence of Western thought and the logic they build; so that the groups will accept the hadith if it is rational.